Virtual Laboratory: Using Electronic Workbench as Alternative Learning Physics in Covid-19 Mass Pandemic - Mafudi, Innal; Handhika, Jeffry (Impulse: Journal of Research and Innovation in Physics Education, 2021)
The purpose of this research is to describe the use of assisted virtual laboratories of Electronic Workbench (EWB) in physics experiments learning. The method in this study used (1) calibration of the results of experiments with theory and (2) analysis of user responses to EWB in practicum activities. The study concluded that: 1) EWB is easy to use for practical learning, 2) capacitive reactance values obtained from calculations and observations following the theory (close to the same), 3) the time needed for one-time trial data retrieval until the analysis phase in this practicum activity is 10 minutes means that the experiment with EWB is very efficient. Based on the results obtained indicate that EWB is feasible to use as an alternative to physics learning in the mass pandemic COVID-19.